Handheld loading to enhance horizontal jump performance In female netball players - McKenzie, C. R.; Brughelli, M.; Whatman, C.; Brown, S. R. (Journal of Australian Strength and Conditioning, 2017)
The purposes of this study were to determine the acute effects of handheld loading on horizontal jump distance and biomechanics during a single standing horizontal jump in female netball players, and to determine individualised optimum loads relative to body mass (BM), for enhancing jump distance. Twelve netball players performed single, standing horizontal jumps while holding load in each hand. The loaded jump conditions included: baseline (0 kilograms (kg)), 2 kg, 4 kg, 6 kg, 8 kg, and 10 kg. A significant increase in jump distance was found at the 4 kg load. Distance increased on average from 171 ±15.3 centimetres (cm) to 177 ±15.4 cm (Effect size [ES]=0.39, p=0.04). The handheld loads of 4 kg and 10 kg produced notable increases in vertical and horizontal concentric ground reaction forces (GRF) (ES=0.25-0.62 (4 kg) and 1.19-0.22 (10 kg)). The predicted optimal relative load to enhance jump distance was 6.4 ±4.0 % BM, producing an increase in jump distance of 9.5 ±6.8 cm (ES=0.61). In conclusion, handheld loading enhanced horizontal jump performance in female netball players, most likely through an increase of concentric GRF's. These findings could be used by strength and conditioning coaches, trainers and athletes to provide an enhanced overload stimulus to develop lower body power. Such overload stimulus should be specific to sports or athletic movements that require horizontal force production.